0384 Clinical Utilization of a CSF Orexin Test: First Two Years of Data from Mayo Clinic. (25th May 2022) - Ruoff, Chad; Louis, Erick St; Cheung, Joseph; Carvalho, Diego; Larson, Bethany; Silber, Michael; Kotagal, Suresh; Krahn, Lois; Bornhorst, Joshua
Abstract: Introduction: Orexin deficiency in cerebrospinal fluid (CSF) was first reported in human narcolepsy in 2001, included in diagnostic criteria for narcolepsy in 2014, and made clinically available at the Mayo Clinic in 2019. The purpose of this publication is to report orexin test utilization and results, and other clinically relevant findings from patients evaluated at Mayo Clinic. Methods: We retrospectively reviewed CSF orexin samples and clinical records from patients evaluated at Mayo Clinic from 2019 to 2021. Results: A total of 98 internal samples (Rochester, n=56; Arizona, n=25, and Florida, n=17) from 95 patients (mean age 32.4 +/- 16.6 years with 20 %, 52 %, and 28 % of patients < 18, 18 – 40, and > 40 years, respectively, at time of CSF collection; 62 % female) have been submitted for CSF orexin measurement (mean CSF orexin 335.17 +/- 158.3 pg/ml; deficient < 110 pg/ml, n=11, 64 % <=40 years with mean age 32.9 +/- 17.0 years; intermediate 110 – 200 pg/ml, n=8, 100 % <= 40 years with mean age 21.1 +/- 12.8 years; normal > 200 pg/ml, n=79, 57 % <=40 years with mean age 33.5 +/- 16.7). No significant correlation was found between orexin levels, and time of collection (i.e., diurnal variation), gender, or age. Repeat testing was performed on three individuals (ages 10, 14, and 19 years) with a change in category of orexin level found in one patient from an intermediate to a normal level. Conclusion: Orexin deficiency was found in 12 % of the patients (64 % of the deficient samples were found at ages <= 40 years). This result may reflect the fact that this test is frequently pursued in clinical patients presenting with inconclusive findings and/or comorbidities. Intermediate orexin levels found in 8 % of the samples (100 % <= 40 years). Although most of the patients tested were female (62.2%) and most were 40 years or younger (72%), no significant correlation was found between orexin levels, and time of collection (i.e., diurnal variation), gender, or age. Support (If Any): none